Perceived destination competitiveness and international tourists response behavior: a case of Langkawi island, Malaysia / Zaliha Zainuddin - Zainuddin, Zaliha (2018)
Destination competitiveness has become a critical issue and creates an increasing challenge in the tourism market. A successful tourism destination should embrace an integrated approach toward many components of tourism system and the competitive advantage of a destination is closely related to the quality of the products offered that determine the quality experience provided by the destination. Researchers determine that the comparative advantage are mostly related to the resources of the tourist destination, tourism image, climate, the countryside, its cultural wealth and its distance from the countries of origin. Due to the different nature of destinations or the purpose/types of tourism activities, it's hard to measure, evaluate, and compare destinations, as in many cases they are unique in their features and cannot be considered identical. Therefore, in analysing the competitiveness of tourism destinations, it is necessary to include the level of satisfaction of visitors and the tourism image as a paradigm of destination competitiveness in the global tourism market. With that, this study investigates the relationship between perceived destination competitiveness attributes and the international tourists' response behavior which is mediated by the tourism images and satisfaction using Langkawi Island, Malaysia as study contextual setting. This study is structured through a self administered questionnaire survey with the individual's international tourists who visited the Langkawi Island using Langkawi international airport as venue for data collection. A total 384 usable questionnaires were successfully collected. With the various statistical analyses ranging from frequency, descriptive, inferential and the Multivariate Structural Equation Modeling (SEM) via Partial Least Square (PLS- SEM) used to answer the objectives, research questions and hypotheses, some useful insights pertaining to the issues investigated was significantly obtained. The results provide evidence that destination competitiveness attributes that are inherited, created and supporting resources influence the international tourists level of satisfaction. Inherited, created and supporting resources are also giving strong impact to or uplifting the tourism images that are destination, country and hotel image despite slightly influence the international tourists' response behaviour (revisit or word of mouth). In addition, the international tourist satisfaction and tourism images also positively giving impact to their response behaviour. These results without doubt expands the existing tourism destination competiveness studies and contributes to the academic and the managerial or practical perspectives. The academic aspect is generated through theoretical contributions whereas the empirical and practical contribution without an exception is closely connected to the destination local authority, hotel and tourism operators and related government authorities.